2022
DOI: 10.1039/d2nj01686a
|View full text |Cite
|
Sign up to set email alerts
|

Zinc(ii) Schiff base complexes as dual probes for the detection of NH4+ and HPO42− ions

Abstract: Three novel Zn(ii) Schiff base complexes were obtained by solvent evaporation technique. 1 and 2 show selectively recognition of NH4+ and HPO42− accompanied with an efficient fluorescence “turn off” phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…And it conforms to the Stern–Volmer ( I 0 / I = 1 + K SV [M]) equation when the HPO 4 2– concentration was in the range of 20.0 to 55.0 μM, where I 0 was the initial luminescence intensity, I was the luminescence intensity after the addition of HPO 4 2– , [M] was the concentration of HPO 4 2– , and K SV was the Stern–Volmer constant. The linear relationship was y = −12655.1836 x – 0.0630, R 2 = 0.9934, and the detection limit was 7.8 × 10 –8 M (Figure a), which was lower than what has been reported in the literature. In the anti-interference experiment, we found that the presence of other anions did not affect the response of complex 1 to HPO 4 2– (Figure b). In addition, we conducted cyclic testing on complex 1 and found that its fluorescence intensity could be restored after four cycles after repeated washing (Figure S8c).…”
Section: Resultsmentioning
confidence: 67%
“…And it conforms to the Stern–Volmer ( I 0 / I = 1 + K SV [M]) equation when the HPO 4 2– concentration was in the range of 20.0 to 55.0 μM, where I 0 was the initial luminescence intensity, I was the luminescence intensity after the addition of HPO 4 2– , [M] was the concentration of HPO 4 2– , and K SV was the Stern–Volmer constant. The linear relationship was y = −12655.1836 x – 0.0630, R 2 = 0.9934, and the detection limit was 7.8 × 10 –8 M (Figure a), which was lower than what has been reported in the literature. In the anti-interference experiment, we found that the presence of other anions did not affect the response of complex 1 to HPO 4 2– (Figure b). In addition, we conducted cyclic testing on complex 1 and found that its fluorescence intensity could be restored after four cycles after repeated washing (Figure S8c).…”
Section: Resultsmentioning
confidence: 67%
“…Another type of tridentate Schiff base has been designed by salicylaldehyde derivatives with various amino-acids in our group. The synthesis route has been indicated in Scheme . The advantages of this type ligand are facile synthesis and “green” components, which are really environmental-friendly Schiff base suitable for applications in many fields.…”
Section: Effect Of Schiff Base Design On Ion Sensingmentioning
confidence: 99%
“…The synthesis route has been indicated in Scheme 1. 40 The advantages of this type ligand are facile synthesis and "green" components, which are really environmental-friendly Schiff base suitable for applications in many fields. Their coordination complexes could be easy to construct and to tune their structures through the changes of synthesis conditions.…”
Section: Effect Of Schiff Base Design On Ion Sensingmentioning
confidence: 99%
See 1 more Smart Citation